Bilateral test for potential subluxation of the DRUJ - Hahn, Peter; Wolf, Maya Barbara; Unglaub, Frank (Archives of orthopaedic and trauma surgery, 2013)
Untreated distal radioulnar joint (DRUJ) instability can lead to arthritis of the DRUJ. To date, however, the clinical determination of DRUJ instability still represents a challenge. We developed a new clinical test to determine its stability. This works by directly observing the ulnar head’s dynamic behavior during active pro-supination or testing the DRUJ’s static stability at different grades of rotation. With the test results, the examiner gains a better understanding of the ulna head’s behavior during rotational movements and how that compares to that of the uninjured side.
Gesehen am 25.03.2021